A STUDY OF THE EFFECT OF ORAL INGESTION OF SILVER FOIL ON LIPID FRACTIONS IN CHICKENS - JAIN, MILI (International Journal of Current Pharmaceutical Research, 2025)
Objective: Silver foil is widely used in Ayurvedic and Unani medicine for various therapeutic purposes, including cardiovascular health. Previous reports have suggested a hypolipidemic effect of silver. This study aimed to evaluate the impact of orally administered silver foil on lipid metabolism in young male chicks. Methods: A total of 50 male chicks (approximately 1 kg body weight) were divided equally into control and experimental groups. The experimental group received 15 mg of silver foil mixed with 1 g of mawa sweet once daily for 10 days. Controls were untreated. After the treatment period, all chicks were sacrificed, and blood samples were collected in heparinized vials. Plasma was separated and analysed for lipid fractions, including total lipids, phospholipids, triglycerides, total cholesterol, HDL-cholesterol, VLDL-cholesterol, and LDL-cholesterol. HDL-cholesterol to total cholesterol ratio was also calculated. Statistical analysis was performed using Student’s paired t-test. Results: Silver analysis revealed 99.5% purity in the foil. Silver levels in the blood and plasma of treated chicks were significantly higher, indicating systemic absorption (4.7 times in blood, 4.4 times in plasma). The experimental group showed significant reductions in total lipids, phospholipids, triglycerides, total cholesterol, LDL-cholesterol, and VLDL-cholesterol, alongside a significant increase in HDL-cholesterol and HDL-C/TC ratio. No signs of toxicity were observed, and body weight increased during the study. Conclusion: These findings suggest that oral ingestion of silver foil exerts a hypolipidemic effect, notably increasing HDL-cholesterol and reducing atherogenic lipid fractions. Silver foil may hold potential as a natural therapeutic agent for preventing or mitigating atherosclerosis.